Emergence pattern of horseweed (Erigeron canadensis L.) accessions across Nebraska. (22nd October 2022) - Mobli, Ahmadreza; Oliveira, Maxwel; Butts, Liberty; Proctor, Chris; Lawrence, Nevin; Werle, Rodrigo
Abstract: Horseweed is a North American indigenous plant species commonly found in Nebraska cropping systems. Horseweed management is challenging because of horseweed's prolific seed production, long-distance seed dispersal via wind, competitiveness, and rapid evolution of herbicide resistance. Understanding the horseweed emergence pattern across Nebraska can contribute to implementing effective and more sustainable tactics to minimize its impact on cropping systems. Field studies were conducted during fall and spring from 2016 to 2018 in Lincoln (corn and soybean), North Platte (wheat stubble and soybean), and Scottsbluff (corn and fallow) to investigate the emergence pattern of horseweed accessions from Lincoln, North Platte, and Scottsbluff, NE. Results show that most horseweed seedling emergence occurred in fall (99%) and only a few seedlings emerged in spring across locations, except in the wheat stubble experiment at North Platte, where higher spring emergence was detected (3% to 22%). In four out of six experiments, the density of total emerged seedlings of each accession was greatest when established in their site of origin. Our results suggest that late fall and/or early spring is likely the best timing for horseweed management across Nebraska.